The Effect of Providing Supplementary Food Made from Local Foods on the Nutritional Status of Stunted Toddlers - Mahmudah Khurotul Aini; Ani Margawati; Sri Winarni (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this research is to determine the effect of providing additional food made from local food on the nutritional status of stunted toddlers in Kedungbanteng District, Tegal Regency. This type of research is a quasi-experimental design with a one group pretest posttest design where the design does not have a control group. Research time is June - December 2022. The research was conducted in 5 villages in the Kedungbanteng Community Health Center area which are running the Rumah Pelita program in 2022. The research subjects were 116 stunted toddlers aged 6-59 months. The results of the study found that there was no difference between the Z score based on the Weight For Height (WHZ) index indicator before and after being given additional food made from local food for 90 days (p > 0.05), there was a difference between the Z score based on the Weight for Age index indicator (WAZ) before and after being given additional food made from local food for 90 days (p < 0.05) and there is a difference between the Z score based on the Height for Age (HAZ) index indicator before and after being given additional food made from local food for 90 days ( p < 0.05). Thus, it was concluded that providing additional food made from local food with a snack menu with a 4 star and modisco concept for 90 days had a significant influence on changes in nutritional status based on weight for age and height for age